A study on security of mosque / Nor Hasnida Ab Halim - Ab Halim, Nor Hasnida (Faculty of Architecture, Planning and Surveying, 2013)
This research is to analysis the effectiveness of the management mosque and examines the level in security and safety from theft. It will be focused on an issue of theft and security of mosque that restricted in mosque at Selangor, Kuala Lumpur and Putrajaya.